2016
DOI: 10.3329/bjvm.v14i1.28850
|View full text |Cite
|
Sign up to set email alerts
|

Occurence and Antibiogram of Salmonella Spp. In Raw and Fermented Milk in Zaria and Environs

Abstract: Salmonellosis is an important food-borne disease affecting both humans and animals. The aim of this study was to determine the occurrence and antibiogram of Salmonella species from raw and fermented milk. The results showed that out of the 350 milk samples examined 14 (4.0%) were positive for salmonella. The prevalence of Salmonella is higher in raw milk (4.6%) than in fermented milk (3.4%) with no statistical difference (P>0.05) between them. The prevalence of both raw (75.0%) and fermented milk (83.33%) is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
0
8
1
Order By: Relevance
“…isolated from milk samples were 100% sensitive to gentamicin, neomycin and ciprofloxacin, and 100% resistant to erythromycin, doxycycline and amoxicilin. Other authors also found Salmonella isolates of raw and fermented milk origin as 100% sensitive to ciprofloxacin and gentamicin and resistant to erythromycin (85.7%) and amoxicillin (78.6%) (Tamba et al, 2016;Munsi et al, 2015).…”
Section: Discussionmentioning
confidence: 90%
“…isolated from milk samples were 100% sensitive to gentamicin, neomycin and ciprofloxacin, and 100% resistant to erythromycin, doxycycline and amoxicilin. Other authors also found Salmonella isolates of raw and fermented milk origin as 100% sensitive to ciprofloxacin and gentamicin and resistant to erythromycin (85.7%) and amoxicillin (78.6%) (Tamba et al, 2016;Munsi et al, 2015).…”
Section: Discussionmentioning
confidence: 90%
“…Creek road Mile one Rumuokoro revealed a 14(100%) susceptibility to Salmonella spp. to the antibiotic as reported by Tamba et al, [28] in Zaria, Nigeria. The report of Islam et al [27] is not in agreement with the findings in this study, Islam et al [27] reported 16(100%) susceptibility of Salmonella spp.…”
Section: Spp Count Of the Various Sample Parts From The Three Marketsmentioning
confidence: 55%
“…recorded corroborates report by Selvaraj et al, [33] The underlying mechanism of β-lactam antibiotic resistance is through the production of βlactamases. These enzymes function by hydrolysing the β-lactam ring by breaking the amide linkage, thereby disabling their capability of inhibiting bacterial cell wall synthesis [28]. Previously, it was known that ESBL-producing bacteria thrived commonly in hospital and clinical settings where extensive use of antimicrobial drugs and agents assisted in the development of their antimicrobial resistance [33].…”
Section: Spp Count Of the Various Sample Parts From The Three Marketsmentioning
confidence: 99%
“…This result is in sharp disagreement with previous studies that revealed a 14(100%) susceptibility to Salmonella spp. to the antibiotic reported by Tamba et al [21] in Zaria, Nigeria. Islam et al [20] also reported an alteration to the findings in this study with their 16(100%) susceptibility of Salmonella pp.…”
Section: Resultsmentioning
confidence: 84%